Plasma-sprayed thermal barrier coatings: numerical study on damage localization and evolution - K. Slámečka; P. Skalka; L. Čelko; J. Pokluda; L. Saucedo-Mora; T. J. Marrow; U. Thandavamoorthy (Fracture and Structural Integrity)
Thermal barrier coatings (TBCs) are advanced material systems used to enhance performance and in-service life of components operated at high temperatures in gas turbines and other power-generation devices. Because of complexity, numerical methods became important tools both for design of these coatings and for in-service life estimations and optimization. In this contribution, two main features that affect the TBCs’ performance, namely the roughness of the bond coat and the microstructure of the ceramic top coat, are discussed based on Finite Element Method (FEM) and Finite Element Microstructure MEshfree (FEMME) simulations that were used to calculate stresses and assess damage within the coating. Roughness data obtained from plasma-sprayed CoNiCrAlY + YSZ coated samples are supplemented to discuss assumptions and results of employed numerical models.